Emergent levels and spaces in studies of active citizenship: A morphogenetic analysis - Weryński, Piotr (Journal of Public Governance, 2016)
The paper focuses on the issues of emergent levels of social reality and the morphogenetic relationships between the social and cultural structure and the agency, as well as on their epistemological and methodological consequences which provide us with theoretical grounds for researching the patterns of civil activity and the functioning of the public sphere. The author attempts to determine how to research complex multi-level emergent phenomena and socio-economic processes in the field of active citizenship.